2002
DOI: 10.1016/s0014-5793(02)02882-x
|View full text |Cite
|
Sign up to set email alerts
|

Transposon‐like Correia elements: structure, distribution and genetic exchange between pathogenic Neisseria sp

Abstract: Correia elements are a prominent feature of all four Neisseria genome sequences. We report an in silico analysis of the structure and genomic distribution of these elements and some preliminary biochemical data. Correia elements fall into four major families, distinguished by a 50 bp internal deletion and ¢ve point mutations. The elements resemble a transposon with 25 bp inverted repeats and a TA duplication at the target site. Within the element there is a functional integration host factor binding site. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 21 publications
2
99
0
Order By: Relevance
“…Unlike SDR elements, the previously described ERIC/IRU (De Gregario et al 2005;Wilson and Sharp 2006), RSA (Bachellier et al 1999), and BoxC (Bachellier et al 1999) elements in enteric bacteria, RUP (Oggioni and Claverys 1999) and boxAB n C (Martin et al 1992;Knutson et al 2006) elements in Streptococcus, and NEMIS (Mazzone et al 2001) and SRE/Correia (Buisine et al 2002) elements in Neisseria are all relatively long, imperfect palindromes possibly derived from transposons.…”
Section: Do Sdr Elements Function As Rna?mentioning
confidence: 96%
See 1 more Smart Citation
“…Unlike SDR elements, the previously described ERIC/IRU (De Gregario et al 2005;Wilson and Sharp 2006), RSA (Bachellier et al 1999), and BoxC (Bachellier et al 1999) elements in enteric bacteria, RUP (Oggioni and Claverys 1999) and boxAB n C (Martin et al 1992;Knutson et al 2006) elements in Streptococcus, and NEMIS (Mazzone et al 2001) and SRE/Correia (Buisine et al 2002) elements in Neisseria are all relatively long, imperfect palindromes possibly derived from transposons.…”
Section: Do Sdr Elements Function As Rna?mentioning
confidence: 96%
“…Neither convention seemed suitable for the elements described in this report, as they may be found in different genera and do not share a common structure. SRE (small repetitive elements) (Buisine et al 2002) is less restrictive, but we would like to maintain a distinction between tandem repeats and repeats well separated on the genome. We have therefore opted for a name that captures only the essential characteristics-small dispersed repeats (SDR)-and have used it as a prefix for specific families, as Tn is used for transposon names.…”
Section: Why Invent a New Name For Families Of Dispersed Repeats?mentioning
confidence: 99%
“…Transposons are important in the spread of antibiotic resistance and as natural genomic engineers: most pathogenic bacteria, for example, have many transposons which function in phase variation and mobilization of pathogenicity islands [e.g. (2)]. During the course of evolution, transposons have diversi®ed to provide functions ranging from HIV integrase to the bene®cial V(D)J recombination machinery (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…1). CREEs have been divided into four families (a, a9, b and b9), distinguished by a 50 bp internal deletion and five point mutations (Buisine et al, 2002). In N. meningitidis strain MC58, the downstream region of nmb0088 contains a Meningococcal antigen characterization 155 bp a-family CREE with 26 bp terminal inverted repeats.…”
Section: Results Nmb0088 and Deduced Protein Featuresmentioning
confidence: 99%
“…It was suggested that these repetitive arrays may encourage sequence variation in neighbouring genes by increasing the frequency of recombination with exogenous DNA (Bentley et al, 2007). Among the most abundant repeat types are the CREEs, which are often located upstream of genes (Liu et al, 2002;De Gregorio et al, 2003a), have been shown to affect gene expression (De Gregorio et al, 2003b), and may be transposable or mobilizable (Buisine et al, 2002). The downstream CREE reported in the present study could also be involved in the expression of NMB0088 since a family of long CREEs has been considered to be a transcriptional terminator in the dcw cluster of N. gonorrhoeae CH811 (Francis et al, 2000).…”
Section: Meningococcal Antigen Characterizationmentioning
confidence: 99%